PENGGUNAAN ALAT PERAGA KONKRIT U PENGGUNAAN ALAT PERAGA KONKRIT UNTUK PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA TENTANG KONSEP BANGUN RUANG DI KELAS VI SD NEGERI 81 / II MUARA BUNGO - suwondo suwondo (Jurnal Tunas Pendidikan, 2021)
The formulation of the problem is, Can the use of concrete teaching aids increase the activeness of class VI students of SD Negeri 81/II Muara Bungo in learning Mathematics about the concept of building space? And, can the use of concrete teaching aids improve learning outcomes in mathematics about the concept of spatial structure in sixth grade students of SD Negeri 81/II Muara Bungo? The purpose of this study is to describe the use of concrete teaching aids in mathematics learning can increase student activity and to describe the use of concrete teaching aids in mathematics learning to improve student learning outcomes. The research subjects were the sixth grade students of SD Negeri 81/II Muara Bungo, totaling 23 students consisting of 7 male students and 16 female students. This research cycled with four stages, namely planning, implementation (action), observation (observation) and reflection (reflection). The data in this study were obtained through tests. The test results showed an increase in the class average value from the initial condition which was only 63.5 with a 34.7% completeness level to 67.8 with a 60.9% completeness level after the first cycle of action. After the second cycle of action, the average results student learning increased again to 82.6 with a 100% completeness rate. In conclusion, the use of concrete teaching aids can increase the activity and learning outcomes of Mathematics about the concept of building space in grade VI students of SD Negeri 81/II Muara Bungo.